Does leukocyte-platelet-rich fibrin (L-PRF) cause long term acceleration in the rate of canine retraction? A split-mouth, two-arm parallel group, randomized control trial - Seema GUPTA; Eenal BHAMBRI; Manish SHARMA; Mubasshir Ahmed SHAIKH; Amit ZOPE; Bhushan THOKE; Monika SOROKHAIBAM (Dental Press Journal of Orthodontics, 2023)
ABSTRACT Objective: The present study was conducted to investigate the effects of leukocyte-platelet-rich fibrin (L-PRF) on the rate of maxillary canine retraction for a period of 5 months. Methods: A split-mouth study was conducted on 16 subjects (9 males and 7 females; age range 17-25 years; mean age, 21.85±2.45 years) who required therapeutic extraction of bilateral maxillary first premolars. After the initial leveling and alignment, L-PRF plugs were placed in a randomly selected extraction socket (Experimental Group), and the other side served as a control (Control Group). Canine retraction was carried out by the activation of nickel-titanium (NiTi) closed-coil springs delivering 150 g of force. The rates of canine movement, canine rotation, tipping, root resorption, and molar movement were assessed at monthly intervals for five months (T0-T5). Pain, swelling and discomfort accompanying the procedure were assessed using a Likert scale. Results: The study revealed a significant increase in the rate of canine movement on the experimental side in the first two months, and significant molar anchorage loss was observed only in the first month for control side. There were no statistically significant differences between the groups regarding canine rotation, tipping, probing depth, root resorption, and pain perception. Conclusions: The use of L-PRF plugs in extraction sockets considerably enhanced the rate of canine movement only in the first two months, and long-term efficacy was not observed in this study.